2005
DOI: 10.1158/0008-5472.can-05-0309
|View full text |Cite
|
Sign up to set email alerts
|

RAD001 (Everolimus) Improves the Efficacy of Replicating Adenoviruses that Target Colon Cancer

Abstract: Selectively replicating adenoviruses have the potential to cure cancer but have shown little efficacy in clinical trials. We have tested the ability of the mTOR kinase inhibitor RAD001

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 52 publications
3
63
0
Order By: Relevance
“…Another recently used strategy to augment oncolytic virus therapy is to target the tumor microenvironment (Rhim and Tosato, 2007). Inhibition of angiogenesis with bevacizumab, sunitinib, cyclic arginine-glycine-aspartic (cRGD) peptide or mammalian target of rapamycin (mTOR) inhibitors has been reported to enhance the anti-tumor effects of oncolytic viruses (Homicsko et al, 2005;Kurozumi et al, 2007;Libertini et al, 2008;Kottke et al, 2010). Since bortezomib inhibits nuclear factor kB activity, reduces vascular endothelial growth factor (VEGF) levels and decreases angiogenesis (Sunwoo et al, 2001;Nawrocki et al, 2002;Roccaro et al, 2006), modulation of vascular permeability may also account for some of the promising activity observed in vivo with the Reolysin/bortezomib combination.…”
Section: Discussionmentioning
confidence: 99%
“…Another recently used strategy to augment oncolytic virus therapy is to target the tumor microenvironment (Rhim and Tosato, 2007). Inhibition of angiogenesis with bevacizumab, sunitinib, cyclic arginine-glycine-aspartic (cRGD) peptide or mammalian target of rapamycin (mTOR) inhibitors has been reported to enhance the anti-tumor effects of oncolytic viruses (Homicsko et al, 2005;Kurozumi et al, 2007;Libertini et al, 2008;Kottke et al, 2010). Since bortezomib inhibits nuclear factor kB activity, reduces vascular endothelial growth factor (VEGF) levels and decreases angiogenesis (Sunwoo et al, 2001;Nawrocki et al, 2002;Roccaro et al, 2006), modulation of vascular permeability may also account for some of the promising activity observed in vivo with the Reolysin/bortezomib combination.…”
Section: Discussionmentioning
confidence: 99%
“…Although rapamycin in conjunction with other viruses (e.g., myxoma virus, vaccinia virus, or adenovirus) augment oncolysis (23,(33)(34)(35)(36), the molecular mechanism by which this process occurs remained elusive. Autophagy and the antiangiogenic effect induced by rapamycin were postulated to promote viral oncolysis (35,37). Here we demonstrate that the inhibition of systemic type I IFN production by rapamycin is the primary mechanism by which VSV ΔM51 (and most likely the other oncolytic viruses) exhibits superior therapeutic efficacy against MGs compared with VSV ΔM51 or rapamycin alone.…”
Section: Discussionmentioning
confidence: 99%
“…One could imagine the creation of similar E4-ORF1 and E4-ORF4 adenoviral mutants that are deficient in activation of mTOR, in order to specifically treat tumors with increased mTOR activity (O'Shea et al, 2005b). Paradoxically, it should be noted that it has also been shown that the mTOR inhibitor RAD001 increases the efficacy of replicating adenoviruses used for colon cancer ablation (Homicsko et al, 2005).…”
Section: Viruses and Mtormentioning
confidence: 99%